Zagadnienie świadomości we współczesnej analitycznej filozofii umysłu - GOMUŁKA, Jakub (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2013)
My article deals with the problem of consciousness in the contemporary analytic philosophy of mind. In its ﬁ rst part I present the historical background of the problem, namely the Cartesian dualism, and the rise and development of cognitive sciences and neurosciences. I explain Ned Block’s «phenomenal consciousness» / «access consciousness» dichotomy, the concept of «explanatory gap» and, of course, the famous concept of qualia. The second part concerns the arguments for and against the irreducibility of (phenomenal) consciousness and qualia like Frank Jackson’s Knowledge Argument and its critique by David Lewis and Daniel Dennett. The third part is devoted to the idea of so-called “new mysterians” (e.g. Colin McGinn). In my opinion McGinn’s standpoint offers a tempting «middle way» between reductionism and anti-reductionism. However, I ﬁ nd his solution unacceptable due to its rampant idealistic assumption that there can be a physical theory unavailable for our cognitive abilities. Such a position can be dubbed «an sich physicalism» – after Kantian concept of Ding an sich – and it must be rejected for any thinker who rejects the possibility that the latter concept can be intelligible. Therefore at the end of my paper I introduce an idea of «meta-mysterianism,» another conception of the «third way» avoiding both reductionism and antireductionism in the analytic philosophy of mind.